A hundred million dollars a day - Field, Michael (London : Sidgwick & Jackson, 1975)
This book is about OPEC money - petro dollars which is concerned with the money of four Arabian Peninsula oil producers, Saudi Arabia, Kuwait, Abu Dhabi and Qatar, which are now receiving far more revenues than they can spend and are commonly regarded as the 'surplus' OPEC states.
Includes index.
occ 16/01/2019
Loans
Keywords: Petroleum industry and trade; Capital investments; Arab countries